THEORETICAL AND PRACTICAL ASPECTS CONCERNING THE ELECTION OF THE PRESIDENT OF ROMANIA - Oana SARAMET (Challenges of the Knowledge Society, 2016)
According to art.81 of Romanian Constitution, the President of Romania shall be elected by universal, equal, direct, secret and free suffrage. The candidate who, in the first ballot, obtained a majority of votes of the electors entered on the electoral lists shall be declared elected. If no candidate has obtained such majority, a second ballot shall be held between the first two candidates highest in the order of the number of votes cast for them in the first ballot. The candidate having the greatest number of votes shall be declared elected. At present, according to Romanian legislation, the electors entered on the electoral lists can only vote at polling stations, even if some citizens are abroad. Unfortunately, Romanian regulations in electoral matters did not recognize the electronic voting or postal voting. Last year, media from around the world showed thousands of Romanian citizens from abroad who stood in long lines to vote at Romanian diplomatic offices abroad. But any participatory democracy means guaranteeing to its citizens the right to vote, not only theoretical but also practically, providing them the most effective and modern ways of voting.